Julius Scott's Masterless Caribbean and the Force of Its Common Wind. Issue 3 (29th June 2020) - Soriano, Cristina
Abstract: The 2018 publication of Julius S. Scott's The Common Wind: Afro-American Currents in the Age of the Haitian Revolution inspired a renewed focus on the reverberations of the Haitian Revolution. Here, six scholars of the Atlantic World and the Age of Revolutions consider the historiographical implications of The Common Wind and remind us how the Haitian upheaval belongs at the very center of the ripples of modernity that spread across the globe from the revolutionary Atlantic.